IMPLEMENTASI PHYSICAL DISTANCING : PENGELOLAAN PEMBELAJARAN PADA ANAK USIA DINI MELALUI PEMANFAATAN PERANGKAT MEDIA SOCIAL - Faizin Faizin; Shafiah Shafiah (Universitas Islam Lamongan, 2020)
This study aims to analyze the management of physical distancing in learning activities in early childhood in Raudlatul Athfal (RA) Tania, Paiton, Probolinggo, through social media tools. This research uses a qualitative approach with case study. The results showed that; Management of learning in early childhood through the use of social media tools in Raudlatul Athfal (RA) Tania, Paiton, Probolingo, East Java as follows; Making learning planning designs during the Covid-19 pandemic, implementing these plans in online learning, monitoring the implementation of learning, giving rewards and punishments and conducting periodic evaluations.